The CD4+/CD8+ Ratio in Pulmonary Tuberculosis: Systematic and Meta-Analysis Article - Yongmei Yin; Jie Qin; Yaping Dai; Fanwei Zeng; Hao Pei; Jun Wang (Tehran University of Medical Sciences, 2015)
Background: The ratio of CD4+/CD8+ has been used as a clinically index to evaluate patients' immunity. Numerous researchers have studied CD4+/CD8+ ratio in pulmonary tuberculosis (PTB) patients. However, the change of CD4+/CD8+ ratio remains controversial. We present a meta-analysis of 15 case-control studies to identify the change of CD4+/CD8+ ratio in PTB patients. Methods: We assessed heterogeneity of effect estimates within each group using I2 test. Subgroup analysis was performed to explore the potential source of heterogeneity. To investigate further the potential publication bias, we visually examined the funnel plots. For robustness of results, we performed sensitivity analysis by removing studies. Data entry and analyses were carried out with RevMan 5.2 (The Nordic Cochrane Centre). Results: Twelve peripheral blood studies were categorized into two subgroups. Eight studies presented a significant decrease of CD4+/CD8+ ratio in PTB cases compared to healthy subjects (SMD: -0.45; 95% CI -0.65--0.25; I2 = 7%). Other four studies researched on the newly diagnosed patients presented a more seriously and significantly decrease (SMD: -2.17; 95% CI -2.61--1.74; I2 = 37%). The pooled analysis of bronchoalveolar lavage fluid (BALF) studies showed a significant increase of CD4+/CD8+ ratio using Flow Cytometry (FCM) (SMD: 4.75; 95% CI 3.44-6.05; I 2 =0%). Conclusion: The present meta-analysis indicated that there was a synthetic evidence for the reduced CD4+/CD8+ ratio in peripheral blood of PTB patients, especially newly diagnosed cases. However, the CD4+/CD8+ ratio in BALF was increased using method of FCM.